The labor market in Israel, 2000-2016 - Tali Larom; Osnat Lifshitz (IZA World of Labor, 2018)
Following a decline in employment and participation rates during the 1980s and 1990s, Israel managed to reverse these trends during the last 15 years. This was accompanied by a substantial decrease in unemployment. New labor force participants are mostly from the low end of the education distribution, and many are relatively old. They entered the labor force in response to cuts in welfare payments and increases in the mandatory retirement age. Net household income for all population groups has increased due to growth in labor income; however, inequality between households has increased.
Keywords: D31; J08; J21; J24; J31; 330; employment; wages; policy; inequality; Israel